Cyber Resilience Frameworks: Exploring Cyber Resilience Frameworks and Strategies for Organizations to Recover From Cyber Attacks and Maintain Operational Continuity (Cybersecurity and Network Defense Research, 2024)
Cyber attacks have become increasingly sophisticated, posing significant challenges to organizations' cybersecurity postures. In response, organizations are turning to cyber resilience frameworks to enhance their ability to withstand, respond to, and recover from cyber attacks. This paper provides a comprehensive review of existing cyber resilience frameworks, analyzing their key components, strategies, and implementation challenges. By exploring various frameworks such as NIST Cybersecurity Framework, ISO 27001, and others, this paper aims to offer insights into best practices for developing and implementing effective cyber resilience strategies. Additionally, the paper discusses the importance of organizational culture, leadership, and collaboration in building a resilient cybersecurity posture. Practical examples and case studies are used to illustrate the application of these frameworks in real-world scenarios. The paper concludes with recommendations for organizations seeking to enhance their cyber resilience and maintain operational continuity in the face of evolving cyber threats.